Integrating a financial counseling center into the Family Center on the campus of Kansas State University - Foster, Theresa (Theresa Marie) (My University, 2015)
According to recent campus and nation-wide studies, Manhattan and surrounding communities would benefit from a financial counseling center. Previous studies have shown that a large number of students, and members of the general population as well, are at risk for financial problems stemming from credit difficulties, lack of personal financial understanding and money management skills. This paper reports findings from a study that was undertaken to determine the need including relevant background information, interviews, and results of those interviews, for placement of a financial counseling center in the Family Center on campus.
Citation: Foster, T. M. (2001). Integrating a financial counseling center into the Family Center on the campus of Kansas State University. Unpublished manuscript, Kansas State University, Manhattan, KS.
Call number: UNIV HG179 .F67 2001
Sponsored by the Marjorie J. and Richard L.D. Morse Family and Community Public Policy Scholarship
Keywords: Finance, Personal; College students--Finance, Personal; Kansas State University. Family Center; Reports; Reports